The spy saw a cop with a telescope: Who has the telescope? An attempt to understand the basic building blocks of ambiguous PP-attachment sequences - Yan, Mengzhu; Nguyen, Michael Hai (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2019)
This paper explores the problem of ambiguous PP-attachment by extracting information from a PP-attachment corpus using Python. Cases of ambiguous PP-attachment involve sequences of the head words of the following type: verb > noun > preposition > noun. The head nouns of ambiguous PP-attachment sentences, as well as aspects beyond head words, are investigated by testing a number of hypotheses using a corpus of thousands of real-world examples. The hypotheses are partially based on theory and partially on empirical evidence. The results support some theoretical claims while discarding others. For instance, one finding that supports an existing claim is that of-PPs always attach to NPs whose heads are classifiers. This kind of knowledge can be put into practice when parsing natural language.